Anomaloppia mazandaranica (Acari: Oribatida: Oppiidae) n. sp. from Iran - Akrami, Mohammad Ali; Subias, Luis S. (Zootaxa, 2007)
A new species of oribatid mite of the family Oppiidae Sellnick, 1937, Anomaloppia mazandaranica sp. n., is described from Mazandaran province, Northern Iran. The new species is characterized by its long sensillus with a fusiform-clavate head and 6-7 long barbs; interlamellar seta as long as lamellar and rostral setae; notogastral setae finely barbed and seta lm as long as others; and a long solenidion on genu I.